Keeping the faith : religious belief in an age of science - Schoenbaum, Thomas J. (Jefferson, N.C. : McFarland, 2008)
"This book explores the modern relationship between religion and science, highlighting the public backlash over teaching evolution in U.S. public schools as an example of the conflict between religious faith and scientific reason"--Provided by publisher.
The controversy between science and religion -- Creationism and the Constitution -- The world of science -- The world of religion -- The world of philosophy -- Faith and reason.
Includes bibliographical references (p. 203-204) and index.
Keywords: Religion and science